2004
DOI: 10.1038/sj.bjc.6601985
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of weekly oxaliplatin and 24-h infusion of high-dose 5-fluorouracil and folinic acid in the treatment of advanced gastric cancer

Abstract: To investigate the efficacy and safety of combining weekly oxaliplatin with weekly 24-h infusion of high-dose 5-fluorouracil (5-FU) and folinic acid (FA) in treatment of patients with advanced gastric cancer. Patients with histologically confirmed, locally advanced or recurrent/metastatic gastric cancer were studied. Oxaliplatin 65 mg m À2 2-h intravenous infusion, and 5-FU 2600 mg m À2 plus FA 300 mg m À2 24-h intravenous infusion, were given on days 1 and 8, repeated every 3 weeks. Between January 2001 throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 49 publications
4
31
0
Order By: Relevance
“…This represents the typical treatment facilities for cancer patients in Germany. As in three studies on oxaliplatin plus 5-FU/FA in gastric cancer previously published by the French group (Louvet et al, 2002a), the Taiwan group (Chao et al, 2004) and the Frankfurt group (Al-Batran et al, 2004), the majority of patients in our study presented with a good performance status and the median age of 62 years was in the same range as in the three previous trials. Of note, all patients included in our study presented with metastatic disease.…”
Section: Efficacysupporting
confidence: 68%
See 1 more Smart Citation
“…This represents the typical treatment facilities for cancer patients in Germany. As in three studies on oxaliplatin plus 5-FU/FA in gastric cancer previously published by the French group (Louvet et al, 2002a), the Taiwan group (Chao et al, 2004) and the Frankfurt group (Al-Batran et al, 2004), the majority of patients in our study presented with a good performance status and the median age of 62 years was in the same range as in the three previous trials. Of note, all patients included in our study presented with metastatic disease.…”
Section: Efficacysupporting
confidence: 68%
“…This regimen induced an objective tumour reponse in 56% of the evaluable patients. The median TTP and survival were 5.2 and 10.0 months, respectively (Chao et al, 2004). Although data from phase III trials have not yet been presented, in daily practice the combination of oxaliplatin plus 5-FU/FA is increasingly used by many oncologists for the treatment of advanced gastric cancer.…”
Section: Efficacymentioning
confidence: 99%
“…Although the detailed mechanism for oxaliplatin-induced TS gene downregulation needs to be further elucidated, our result is concordant with two previous reports (Raymond et al, 2002;Yeh et al, 2004), which indicated that oxaliplatin could downregulate TS in cancer cells and thus potentiate the efficacy of 5-FU. As oxaliplatin and 5-FU have been shown to be highly synergistic not only in preclinical models (Raymond et al, 1997) but also in subsequent clinical trials (Rothenberg et al, 2003;Chao et al, 2004;Lordick et al, 2005;Schippinger et al, 2005;Cavanna et al, 2006), our data provide important information regarding why the combination of oxaliplatin and 5-FU results in better objective response than single use alone.…”
Section: Discussionmentioning
confidence: 74%
“…In 2005, there were approximately 400 000 new cases and 300 000 deaths from gastric cancer (Yang, 2006). There is currently no established standard regimen for advanced gastric cancer; however, biweekly oxaliplatin plus 5-fluorouracil (5-FU) and folinic acid (FOLFOX) was well tolerated and yielded median survival times of 9.6 -11.4 months in five phase II studies (Louvet et al, 2002;Al-Batran et al, 2004;Chao et al, 2004;De Vita et al, 2005;Lordick et al, 2005). Considerable published evidence suggests that interindividual variation in response to 5-FU results from variations in the thymidylate synthase (TS) mRNA expression levels of the tumour (Longley et al, 2003).…”
mentioning
confidence: 99%